Enlightenment in the eighteenth century and the impact of rationalism in it (Journal of Human Sciences, 2021)
Through this research, we dealt with a topic within the framework of the research on the nature of the Enlightenment and the rational direction in it. The study was limited to the period of the Enlightenment in order to see the role that the mind played in this period "the eighteenth century" and then the possibility of relying on it in building any civilization, so the mind is our way to reach the truth behind the apparent, and we were also exposed to the principles of the age of enlightenment that he advocated, and proceeded from, and the most important one was the principle of freedom. It is well known that the mind was before the age of the Enlightenment under the constraints of its chains with the church, those restrictions prevented "Copernicus" from presenting his theory that changed the world and suppressed the belief that was prevalent. After him, "Galileo" and "Kepler" came to confirm its authenticity; the church did not accept any theory inconsistent with the prevailing religious beliefs. We also discussed through this study the reasons that led to the emergence of the Enlightenment, so the main reason was the domination of the Church as we mentioned earlier, even though the Christian is a heavenly religion that calls for equality between people, while the Church has installed itself as a guardian of this religion and prohibited any ideas that contradict the ideas of Patlimous who said that the universe is fixed and the Earth forms the center of the universe, around which the sun revolves. The ideas and principles of the Enlightenment philosophers and thinkers were influenced by the philosophical ideas - which preceded or coincided with them, such as "Bacon", which relied on his access to scientific facts on extrapolation. And by taking nature as a field in which the mind takes off, and by using freedom as a principle, as the research refuses to submit to any religious or political authority, and by specifying it to advance as a goal and a mean that seeks to provide a better life for this human.